Molecular findings of Colombian patients with type VI mucopolysaccharidosis (Maroteaux-Lamy syndrome) (2016)
ntroduction: Maroteaux-Lamy syndrome, or mucopolysaccharidosis (MPS) type VI, is an autosomal recessive lysosomal storage disease caused by a deficient activity of the enzyme arylsulfatase B (ARSB), required to degrade dermatan sulfate. The onset and progression of the disease vary, producing a spectrum of clinical presentation. So far, 133 mutations have been reported. The aim of this study is to determine the mutations in the ARSB gene that are responsible for this disease in Colombian patients. Results: Fourteen patients with clinical manifestations and biochemical diagnosis of MPS VI were studied, including two siblings. The 8 exons of the gene were directly sequenced from patients' DNA, and 14 mutations were found. 57% of these mutations had not been previously reported (p.H111P, p.C121R, p.G446S, p.*534W, p.S334I, p.H147P, c.900T. >. G, and c.1531_1553del) and 43% had been previously reported (p.G144R, p.W322*, p.G302R, p.C447F, p.L128del, and c.1143-1G. >. C). Of the previously reported mutations, 80% have been associated with severe phenotypes and 20% with intermediate-severe phenotypes. Bioinformatic predictions indicate that the new mutations reported in this paper are also highly deleterious. Conclusions: Most of the Colombian patients in this study had private mutations.